ORGANIZATIONAL-ECONOMIC PROBLEMS OF INTERACTION SYSTEMS OF AVIATION ENTERPRISES PROVIDING THE ACHIEVEMENT OF THE ESTABLISHED LEVEL OF ECONOMIC INDICATORS - T. Rogulenko (Publishing House of the State University of Management, 2017)
General rules for the development of interrelations between structural divisions of the enterprise are presented. The necessity of improvement of existing processes of connections of the organizations used in daily activities with the purpose of their economic development is indicated. The main control body, which is part of the structure of the enterprise, representing the interest of the state customer, is reflected. The need to develop a universal system aimed at ensuring the adoption of management decisions on the management of income and expenditure of the enterprise, which is able to solve the main tasks of management nature, is determined.